2013
DOI: 10.1121/1.4831449
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear acoustic pulse propagation in dispersive sediments using fractional loss operators

Abstract: The nonlinear progressive wave equation (NPE) is a time-domain formulation of Euler’s fluid equations designed to model low-angle wave propagation using a wave-following computational domain [ McDonald et al., J. Acoust. Soc. Am. 81]. The wave-following frame of reference permits the simulation of long-range propagation that is useful in modeling the effects of blast waves in the ocean waveguide. However, the current model does not take into account sediment attenuation, a feature necessary for accurately desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Also, fractional derivatives have lately been applied to model frequency dependent power-law wave attenuation in sediments. 23 Second, we have recently demonstrated that just as non-Hookean materials lead to nonlinear acoustics, time-dependent non-Newtonian materials tend to power law behavior. 24 Interestingly, power-law characteristics are common in materials modeled using fractional derivatives, such as biological media 25− 29 and earth materials.…”
Section: Introductionmentioning
confidence: 99%
“…Also, fractional derivatives have lately been applied to model frequency dependent power-law wave attenuation in sediments. 23 Second, we have recently demonstrated that just as non-Hookean materials lead to nonlinear acoustics, time-dependent non-Newtonian materials tend to power law behavior. 24 Interestingly, power-law characteristics are common in materials modeled using fractional derivatives, such as biological media 25− 29 and earth materials.…”
Section: Introductionmentioning
confidence: 99%